Assessment of Lymph Nodes and Prostate Status Using Early Dynamic Curves with 18F-Choline PET/CT in Prostate Cancer - Mathieu, Cédric; Ferrer, Ludovic; Carlier, Thomas; Colombié, Mathilde; Rusu, Daniela; Kraeber-Bodéré, Françoise; Campion, Loic; Rousseau, Caroline (Frontiers in Medicine, 2015)
Introduction: Dynamic image acquisition with 18F-Choline (FCH) PET/CT in prostate cancer is mostly used to overcome the bladder repletion which could obstruct the loco-regional analysis. The aim was to analyze early dynamic FCH acquisitions to define pelvic lymph node or prostate pathological status. Material and methods: Retrospective analysis was performed on 39 patients for initial staging (n=18), or after initial treatment (n=21). Patients underwent ten-minute dynamic acquisitions centered on the pelvis, after injection of 3-4 MBq/kg of FCH. Whole body images were acquired about one hour after injection using a PET/CT GE Discovery LS (GE-LS) or Siemens Biograph mCT (mCT). Maximum and mean SUV according to time were measured on nodal and prostatic lesions. SUVmean was corrected for partial volume effect (PVEC) with suitable recovery coefficients. The status of each lesion was based on histological results or patient follow-up (>6 months). A Mann-Whitney test and ANOVA were used to compare mean and receiver operating characteristic curve analysis. Results: The median PSA was 8.46 ng/mL and the median Gleason score was 3+4. Ninety-two lesions (43 lymph nodes and 49 prostate lesions) were analyzed, including 63 malignant lesions. In early dynamic acquisitions, the maximum and mean SUV were significantly higher, respectively on mCT and GE-LS, in malignant versus benign lesions (p<0.001, p<0.001). Area under the ROC curve showed a trend to better sensitivity and specificity for early acquisitions, compared with late acquisitions (SUVmax 0.92 versus 0.85 respectively) Mean SUV without PVEC, allowed better discrimination of benign from malignant lesions, in comparison with maximum and mean SUV (with PVEC), for both early and late acquisitions. For patients acquired on mCT, area under the ROC curve showed a trend to better sensitivity and specificity for early acquisitions, compared with late acquisitions (SUVmax AUC 0.92 versus 0.85 respectively). Conclusion: Assessment of lymph nodes and prostate pathological status with early dynamic imaging using PET/CT FCH allowed prostate cancer detection in situations where proof of malignancy is difficult to obtain.